1982
DOI: 10.1007/bf00393441
|View full text |Cite
|
Sign up to set email alerts
|

Lectin synthesis in developing and germinating wheat and rye embryos

Abstract: Wheat (Triticum aestivum L.) and rye (Secale cereale L.) lectins are specifically synthesized during seed formation. They accumulate exponentially in the primary axes in a period coinciding with the development of this complex organ. Since the specific lectin content also increases dramatically, there is apparently an outburst of lectin synthesis during the development of the primary axes. Germinating embryos also synthesize some lectin. The fortunate availability of a highly specific procedure for the isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…2, the precipitin lines formed with WGA and AREL fuse completely, indicating that both embryo lectins are antigenically very closely related. Previous work on cereal embryo lectins revealed that wheat, rye and barley lectins are structurally so closely related that they can exchange subunits with each other in vitro and in vivo [19]. Since WGA and AREL were apparently very similar, both structurally and serologically, experiments were set up to find out wether these two lectins too were able to exchange subunits in vitro.…”
Section: Agropyrum Repcns Embryo Lectin (Arel)mentioning
confidence: 99%
See 2 more Smart Citations
“…2, the precipitin lines formed with WGA and AREL fuse completely, indicating that both embryo lectins are antigenically very closely related. Previous work on cereal embryo lectins revealed that wheat, rye and barley lectins are structurally so closely related that they can exchange subunits with each other in vitro and in vivo [19]. Since WGA and AREL were apparently very similar, both structurally and serologically, experiments were set up to find out wether these two lectins too were able to exchange subunits in vitro.…”
Section: Agropyrum Repcns Embryo Lectin (Arel)mentioning
confidence: 99%
“…Since WGA and AREL were apparently very similar, both structurally and serologically, experiments were set up to find out wether these two lectins too were able to exchange subunits in vitro. Actually, CLAA (which corresponds to the WGA isolectin composed of two identical subunits coded for by the A genome of hexaploid wheat) was used in stead of complete WGA since the latter is already a mixture of six different isolectins [18]. As shown in Fig.…”
Section: Agropyrum Repcns Embryo Lectin (Arel)mentioning
confidence: 99%
See 1 more Smart Citation
“…Then the homogenates were centrifuged (3,000g; 2 min) and the supernatant taken off. Three aliquots of 25 gl were withdrawn for determination of total protein synthesis (measured as incorporation of [35S]cysteine into hot TCA-insoluble material) as described previously (11). To the remainder, an equal volume of Na-acetate buffer (50 nm Na-acetate, 0.1 M NaCl) was added and kept in ice for 30 min.…”
mentioning
confidence: 99%
“…To the remainder, an equal volume of Na-acetate buffer (50 nm Na-acetate, 0.1 M NaCl) was added and kept in ice for 30 min. Then the coagulated material was spun off(5 min, 3,000g) and the resulting supernatant used for affinity chromatography of the lectin on immobilized N-acetylglucosamine (Selectin 1 from Pierce Chemical Company, Rockford, IL) as described previously (11 Blue in a mixture of acetic acid:methanol:water (1:5:5, by vol). Thereafter, the gels were destained with the same solvent.…”
mentioning
confidence: 99%